Effects of the EU's carding system for IUU fishing in its trading partners - Assia Baric; Jinhwan Oh (Global Business & Finance Review (GBFR), 2022)
Purpose: This study investigated the effects of the EU carding system for IUU fishing on its trading partners carded for illegal fishing practices, with the purpose of analyzing the extent to which the carding system affected trade between the EU and third countries identified and penalized for IUU fishing, and to identify factors influencing the likelihood of card removal. Design/methodology/approach: The study used fishery and aquaculture trade data from 2004 to 2020 from the European Market Observatory for Fisheries and Aquaculture Products on 26 carded countries. Major analytic tools applied in this study include OLS, Panel Random Effect, Logit and Probit Models. Findings: The study confirmed that being carded by the EU for IUU fishing significantly negatively impacted countries' fishery trade flows, especially in the case of red cards. Furthermore, increases in capture of wild fish and corruption reduced the likelihood of having the card removed. Research limitations/implications: An important limitation of this study is that it did not account for the influence of other major industry players (such as Japan, USA, China) on the country's overall trade flows. Notwithstanding, it explored how certain variables reduced the likelihood of card removal, finding that countries with higher levels of corruption and fish capture were less likely to have their cards revoked, putting them at a further disadvantage. The findings are especially important in the context of the fishing industry which supports local economies in many developing countries that are usually the target of such coercive measures. Restricted trade flows are especially damaging to small-scale fishers who are often forgotten in the global fight against IUU fishing. This study brings attention to the carding system's potential for trade disruptions and future applications of this sanctioning mechanism should take this under advisement. Originality/value: Studies of the EU carding system's produced effects remain scarce, with existing ones focusing either on individual countries or on the mechanism's general potential for curbing IUU fishing. Considering the global nature of the fishing industry and the harmful potential of the carding system for vulnerable coastal communities, this study attempted to achieve a broader and more in-depth understanding of the EU carding system's effects by examining all countries that were carded for IUU fishing from the enforcement of the IUU Regulation until 2020.
Keywords: 650; IUU fishing; EU carding system; the IUU Regulation; fishery trade; sanctions